Africa Food Safety Index (AFSI), tool for African countries to measure, monitor, and benchmark progress on key food safety indicators - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The African Union (AU) launched its second Comprehensive Africa Agriculture Development Programme Biannual Review, including among its indicators this new index on food safety. The index (https://au.int/sites/default/files/documents/33005-doc-prioritizing_food_safety_in_africa-eng.pdf) was developed by a multidisciplinary team including CGIAR researchers from ILRI.